Calycosin suppresses the activating effect of granulocyte-macrophage-colony-stimulating factor-producing T helper cells on macrophages in experimental atherosclerosis - Xiong, Xiaofang; Huang, Wei; Yang, Xuexue; Wang, Xun; Wu, Beibei; Li, Dongsheng (Frontiers in Pharmacology, 2025)
BackgroundT cells are contributors to atherosclerosis pathogenesis. Granulocyte-macrophage-colony-stimulating factor (GM-CSF)-producing T helper (ThGM) cells, a specialized helper T cell subset that highly expresses GM-CSF but lacks other helper T cell markers, could exacerbate atherosclerosis development. Calycosin has been reported to suppress atherosclerosis progression. However, the effect of calycosin on ThGM cells is unknown. This study was designed to test the calycosin-induced impact on the pro-atherosclerotic function of ThGM cells in a mouse atherosclerosis model.MethodsApolipoprotein E knockout (ApoE−/−) mice were fed a high-fat diet and calycosin. The phenotype and cytokine expression of aortic ThGM cells were assessed by flow cytometry. Calycosin-derived influences on ThGM cell differentiation, proliferation, and function were determined by flow cytometry, quantitative RT-PCR, Immunoblotting, gene silencing assays, and co-culture with macrophages.ResultsAortic ThGM cell frequency was attenuated after calycosin administration. Live aortic ThGM cells, phenotypically featuring CD4+CCR6−CCR8−CXCR3−CCR10+, showed slower proliferation and weaker macrophage-activating capability in calycosin-treated mice. Besides, calycosin repressed in vitro ThGM cell differentiation and subsequently impaired ThGM cell-mediated macrophage activation, oxidized low-density lipoprotein (Ox-LDL) uptake, and foam cell formation. Importantly, calycosin upregulated nuclear receptor subfamily 4 group A member 3 (NR4A3) in ThGM cells. NR4A3 silencing partially restored the function of calycosin-treated ThGM cells.ConclusionCalycosin inhibits ThGM cell activity to suppress ThGM-cell-mediated activation of pro-atherosclerotic macrophages to ultimately ameliorate atherosclerosis progression. Therefore, we revealed a novel mechanism by which calycosin protects against atherosclerosis.